2008
DOI: 10.1620/tjem.215.349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Complex Sleep Apnea Among Japanese Patients with Sleep Apnea Syndrome

Abstract: Sleep apnea syndrome (SAS) is basically divided into two types: obstructive and central SAS. Recently, the concept of complex SAS has been advocated. Complex SAS is defined as SAS that initially manifests as primarily obstructive SAS, but is characterized by the frequent central apneas after the removal of upper airway obstruction. To determine the prevalence and clinical significance of complex SAS among Japanese patients with SAS, 1,312 patients with SAS were enrolled in this study. Diagnosis of central SAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 17 publications
6
28
0
1
Order By: Relevance
“…This is close to results from MORGENTHALER et al [4] and LEHMAN et al [14], but higher than prevalence rates found in recent studies by ENDO et al [12] and JAVAHERI et al [13] (table 7). We could not replicate male dominance and slightly younger age in CompSA, as found by most other authors.…”
Section: Initial Compsasupporting
confidence: 91%
See 3 more Smart Citations
“…This is close to results from MORGENTHALER et al [4] and LEHMAN et al [14], but higher than prevalence rates found in recent studies by ENDO et al [12] and JAVAHERI et al [13] (table 7). We could not replicate male dominance and slightly younger age in CompSA, as found by most other authors.…”
Section: Initial Compsasupporting
confidence: 91%
“…Our sleepiness scores are similar to other results [4,13]. Our sample's age profile differs only from the study of ENDO et al [12], who studied younger patients. All other studies determined CompSA on titration nights or in the titration part of split-night studies.…”
Section: Initial Compsasupporting
confidence: 88%
See 2 more Smart Citations
“…[13][14][15][16][17][18] The number of patients with OSA in the United States is estimated at 15 million. 19 However, some believe that these rates may be an underestimate, since rates of obesity, which is a major risk factor for OSA, has been steadily increasing over recent decades.…”
Section: Rev I E W a Rt I C L E Smentioning
confidence: 99%